2023
DOI: 10.3390/healthcare11121795
|View full text |Cite
|
Sign up to set email alerts
|

MIH and Dental Caries in Children: A Systematic Review and Meta-Analysis

Abstract: (1) Background: Molar-incisor hypomineralization (MIH) is a clinical condition affecting permanent teeth in children, with a documented rising trend in the last two decades. The aim of the present study was to analyze and synthesize the available evidence on caries experience (dmft/DMFT) and MIH in children. (2) Methods: A systematic review and meta-analysis were conducted according to the PRISMA statement. (3) Results: 59 papers published between 2007 and 2022 were included in the qualitative synthesis and 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Similar to Kühnisch et al [12], in our analyses we did not apply adjustments for sex and age because there were no statistically significant differences in these variables between the MIH and non-MIH groups. The results of a recent meta-analysis by Mazur et al revealed a significant correlation between MIH and caries in permanent dentition in children [17]. However, a few researchers have not confirmed this [18,19].…”
Section: Discussionmentioning
confidence: 97%
“…Similar to Kühnisch et al [12], in our analyses we did not apply adjustments for sex and age because there were no statistically significant differences in these variables between the MIH and non-MIH groups. The results of a recent meta-analysis by Mazur et al revealed a significant correlation between MIH and caries in permanent dentition in children [17]. However, a few researchers have not confirmed this [18,19].…”
Section: Discussionmentioning
confidence: 97%
“…The inferior physical properties of MIH-affected enamel have been readily translated to the assumption that MIH-affected dentitions have a higher caries risk than non-affected individuals, but this is not reflected in the literature, where there is an incongruity reported in the relationship between MIH and caries. A recent systematic review evaluated 59 papers between 2007 and 2022 and reported a significant association between MIH and caries lesions diagnosed via the WHO index (mean difference in DMFT 0.56 [0.41, 0.72]) [31]. The clinical significance of this mean difference in DMFT is difficult to interpret, but as it is below 1, it could be argued to be nominal.…”
Section: Dental Cariesmentioning
confidence: 99%
“…Depending on the severity, teeth with MIH may exhibit rapid wear, enamel loss after enamel breakdown and eruption under functional masticatory forces, increased sensitivity to caries, loss of fillings and, above all, severe sensitivity that often causes serious discomfort [ 6 11 ]. In addition, MIH causes a higher risk of caries in children, both in the permanent and primary dentition [ 12 ].…”
Section: Introductionmentioning
confidence: 99%